2021
DOI: 10.3390/en14248329
|View full text |Cite
|
Sign up to set email alerts
|

Water-Cooled Thermoelectric Generators for Improved Net Output Power: A Review

Abstract: Thermoelectric generators (TEGs) have the ability to convert waste heat into electrical energy under unfavorable conditions and are becoming increasingly popular in academia, but have not yet achieved a broad commercial success, due to the still comparably low efficiency. To increase the efficiency and economic viability of TEGs, research is performed on the materials on one hand and on the system connection on the other. In the latter case, the net output power of the cooling system plays a key role. At first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 99 publications
(179 reference statements)
2
7
0
Order By: Relevance
“…When the cooling system uses a heatsink-fan, the electrical output voltage produced by TEG is 6.215 V, but the electrical output will increase if the cooling system uses a water block at 8.232 V. This indicates that the use of a water block cooling system will be more effectively used as a TEG cold surface cooling system because it produces higher voltage performance. This finding is in line with the research conducted by Pfeiffelmann et al [22], the results of the study found that active watercooling should be the method of choice to achieve high electric output generated by TEG.…”
Section: Open Circuit Teg Measurementsupporting
confidence: 92%
“…When the cooling system uses a heatsink-fan, the electrical output voltage produced by TEG is 6.215 V, but the electrical output will increase if the cooling system uses a water block at 8.232 V. This indicates that the use of a water block cooling system will be more effectively used as a TEG cold surface cooling system because it produces higher voltage performance. This finding is in line with the research conducted by Pfeiffelmann et al [22], the results of the study found that active watercooling should be the method of choice to achieve high electric output generated by TEG.…”
Section: Open Circuit Teg Measurementsupporting
confidence: 92%
“…The results indicate a positive effect of the flow velocity on the output voltage and efficiency. Comparing these results to earlier research [45,46], it was found that using stripe-shaped surfaces on the cooling cold side of a TEG module is better than plate-shaped or diamond-shaped surfaces. In these earlier studies, temperature increases in the cooling fluid from the inlet-to-outlet conditions were 8.5, 6.2, and 10.5 • C, respectively, for stripe-, plate-, and diamond-shaped surfaces.…”
Section: Flow Velocitysupporting
confidence: 64%
“…These results demonstrate better efficiency using an M-shaped channel rather than other shapes. It allows for maintenance of a higher temperature differential for heat transfer and therefore a higher output voltage [45][46][47]. In Figure 14, contour plots of the temperature distribution at a plane just below the cold surface of the TEG, for different inlet flow velocities, are presented.…”
Section: Flow Velocitymentioning
confidence: 99%
“…Therefore, we concluded that the use of concentrated optics is not suitable for the EoL PV sandwich, unless the surrounding EVA is removed. As another approach, appropriate water or air-cooling techniques can be applied on the heat sink to enhance the temperature difference between the hot side and cold side of the TEG . These approaches can effectively accelerate the heat dissipation process, leading to an improved overall performance of the EoL PV sandwich/TEG hybrid device.…”
Section: Resultsmentioning
confidence: 99%